STUDI KOMPARASI PENANGANAN COVID-19 ANTARA INDONESIA DENGAN MALAYSIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Siregar, Fitri Oktarina; Firdaus, Emilda; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The State of Indonesia is a unitary state, in carrying out a policy in government affairs that covers cross-provincial or cross-country areas under the authority of the central government and the central government becomes the holder of control over the handling of the pandemic at the national level. However, the central government has many limitations in handling it up to the sub-national level. While Malaysia is a country that adheres to the type of federal state with a democratic monarchy system of government. The Malaysian Federation system consists of a central and state government, where the status of the federal and state states is equal. states are given the widest possible autonomy to administer their regions and in a federal state that power is divided in such a way that the federal government and state governments in certain fields are independent of each other, each state has its own policy in dealing with covid. -19. Various strategies and policies were issued by the governments of Indonesia and Malaysia as well as appropriate steps in dealing with the epidemic that spread throughout the world, the government policies in the form of establishing regulations, government authorities, in the health, education, economic and social fields to reduce the spread of corona virus transmission so that it does not spread. spread widely in society and slow down the rate of covid-19.This research is a normative juridical research, research conducted based on legal materials and legislation. The approach taken includes a library approach, namely by studying books and laws and regulations. The types of data used are primary data types, secondary data sources are data sources derived from books and other regulations. The theory used in this research is comparative law theory and political system theory.From the results of the study, there are two main things that can be concluded where comparing two countries with different government systems certainly have different policies and ways of handling. Indonesia with a unitary state centered on the central government and Malaysia with a federal state where the status of the federal state and the states are equal. The policy disparity between the central government and local governments in handling the COVID-19 disease outbreak in Indonesia is experiencing public discourse and there are still some policy weaknesses in the fields of health, economy, social, education, government authority and regulations established to prevent the spread of COVID-19 are increasing. increase.Keywords: Comparison – Policy – Covid-19 – HAM